Sistem Informasi Administrasi (Si Admin) Unit Kegiatan Mahasiswa (UKM) Menggunakan Metode Extreme Programming - Yunita, Ika Romadoni; Farikhatun, Nofi; Ismiyati, Ragilah; Setiawan, Ito (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Students organizations (UKM) in data administration still uses Google forms and manuals by coming directly to the student affairs room to submit proposals and activity reports. This has an impact on the administration process taking a long time, high error rates, and less effective work. Data that is difficult to combine from forms and manually. Student Affairs also wants all UKM data administration to be system-based so that the data search process is easier and integrated with each other. Therefore, all data administration systems are needed for SMEs so that the problems that have occurred so far can be resolved. The aim of creating an administrative information system (SI ADMIN) is to make it easier for UKM administrators to carry out activities and carry out work programs that have been created. This system will later be integrated with the main student affairs website, which includes several sections such as alumni study tracer, graduate user tracer, job vacancy information and others. The stages in working on SI ADMIN use the extrame programming method. An administrative information system has been successfully created so that existing problems regarding SME administrative management have been successfully resolved. This system has also been tested directly by UKM and student affairs as admin. Based on the tests carried out, it can be concluded that the scenarios tested are in accordance with the expected results.